2014
DOI: 10.1007/s00468-014-1075-1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of boron toxicity on root and leaf anatomy in two Citrus species differing in boron tolerance

Abstract: Key message Typical toxic symptom only occurred in B-toxic C. grandis leaves. B-toxicity induced PCD of C. grandis leaf phloem tissue. The lower leaf free B might contribute to the higher B-tolerance of C. sinensis. Abstract Seedlings of 'Xuegan' (Citrus sinensis) and 'Sour pummelo' (Citrus grandis) differing in boron (B)-tolerance were irrigated with nutrient solution containing 10 (control) or 400 (B-toxic) lM H 3 BO 3 for 15 weeks. Thereafter, the effects of B-toxicity on leaf photosynthesis, chlorophyll, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
50
0
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 46 publications
10
50
0
2
Order By: Relevance
“…In relation to E and C i , these variables presented not significant changes, corroborating with the study by Huang et al (2014) who also did not found modification in E of Citrus sinensis under B excess. Papadakis et al (2004) studying the B toxicity effects in Citrus plants observed decreased in P N /C i , similar with results detected in this research.…”
Section: Ros Frequently Induces Increases In Elsupporting
confidence: 89%
“…In relation to E and C i , these variables presented not significant changes, corroborating with the study by Huang et al (2014) who also did not found modification in E of Citrus sinensis under B excess. Papadakis et al (2004) studying the B toxicity effects in Citrus plants observed decreased in P N /C i , similar with results detected in this research.…”
Section: Ros Frequently Induces Increases In Elsupporting
confidence: 89%
“…The main morpho-anatomical changes promoted by B excess encompasses modifications at root level, such as alteration of root meristems (Choi et al 2007), thickening of hypodermis and deposition of suberin in cortical cells (Ghanati et al 2002), root lignification, which likely represent an attempt by the plant to reduce the intake of B and limit the toxicity to root apparatus. At stem level, B excess can promote the development of cork and collenchyma cells with increased cell wall thickness in loquat (Papadakis et al 2018) and thickening in the cell wall of phloem cells in citrus (Huang et al 2014), mechanisms which reduce the amount of free B and represent a further detoxifying mechanism by storing excessive B in tissues where it could be less harmful. Addressing the effect in leaves, few reports have investigated the morpho-anatomical changes that are provoked by B excess.…”
Section: Physiological and Biochemical Responses To B Excessmentioning
confidence: 99%
“…Boric acid, while affects growth, did not induce apoptosis in breast cancer cells [7]. Studies in flora and insects already pointed to autophagy elevation in boric acid toxicity [9,10], which was behind the reasoning that autophagy might responsible of BA mechanism of action.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of its lethal effects did not involve apoptosis, but it is suspected to be through histone deacetylase inhibition [7,8]. Furthermore, boric acid toxicity was reported to be associated with autophagy in plants and insects [9,10]. While on the other hand, several studies linked histone deacetylase inhibitors (HDACi) with an increased autophagy [11].…”
Section: Introductionmentioning
confidence: 99%